A global value chain of knowledge to end hunger sustainably - Laborde Debucquet, David; Murphy, Sophia; Porciello, Jaron; Smaller, Carin (International Institute for Sustainable Development, 2020)
The UN 2030 Agenda commits governments to evidence-based decision-making (UN General Assembly, 2015). This approach requires efforts to find and catalogue the evidence, then developing methods to analyze and synthesize it. It also means understanding the feasibility of whichever interventions the government identifies, taking into account the policy landscape in which the decision-maker operates. Policy interventions require political support among competing interests in the context of meeting both short- and long-term objectives. Motivated by the need to support tools for evidence-based policy-making, three partner organizations—Cornell University, the International Food Policy Research Institute (IFPRI) and the International Institute for Sustainable Development (IISD)—formed a three-year partnership in 2018 called Ceres2030:Sustainable Solutions to End Hunger. The project is designed to support global development donors to increase the amount and improve the efcacy of their investment of public funds in improving food security and sustainability outcomes.